Targeting Serotonin 2A and Adrenergic α1 Receptors for Ocular Antihypertensive Agents: Discovery of 3, 4‐Dihydropyrazino[1, 2‐b]indazol‐1(2H)‐one Derivatives. (9th July 2018) - Furlotti, Guido; Alisi, Maria Alessandra; Cazzolla, Nicola; Ceccacci, Francesca; Garrone, Beatrice; Gasperi, Tecla; La Bella, Angela; Leonelli, Francesca; Loreto, Maria Antonietta; Magarò, Gabriele; Mangano, Giorgina; Bettolo, Rinaldo Marini; et al.
Abstract: Glaucoma affects millions of people worldwide and causes optic nerve damage and blindness. The elevation of the intraocular pressure (IOP) is the main risk factor associated with this pathology, and decreasing IOP is the key therapeutic target of current pharmacological treatments. As potential ocular hypotensive agents, we studied compounds that act on two receptors (serotonin 2A and adrenergic α1 ) linked to the regulation of aqueous humour dynamics. Herein we describe the design, synthesis, and pharmacological profiling of a series of novel bicyclic and tricyclic N 2‐alkyl‐indazole‐amide derivatives. This study identified a 3, 4‐dihydropyrazino[1, 2‐ b ]indazol‐1(2 H )‐one derivative with potent serotonin 2A receptor antagonism, >100‐fold selectivity over other serotonin subtype receptors, and high affinity for the α1 receptor. Moreover, upon local administration, this compound showed superior ocular hypotensive action in vivo relative to the clinically used reference compound timolol. Abstract : Taking the pressure off : The elevation of intraocular pressure (IOP) is the main risk factor associated with glaucoma. We studied, as potential ocular hypotensive agents, compounds that act on two receptors—serotonin 2A (5‐HT2A ) and adrenergic α1 —both linked to the regulation of aqueous humour dynamics. We identified the 3, 4‐dihydropyrazino[1, 2‐ b ]indazol‐1(2 H )‐one derivative 28 as an effective "dual" 5‐HT2A and α1 antagonist. Compound 28 showed potent ocular hypotensive action in vivo.